2008
DOI: 10.1073/pnas.0802063105
|View full text |Cite
|
Sign up to set email alerts
|

Cidea is associated with lipid droplets and insulin sensitivity in humans

Abstract: adipocyte ͉ Cide ͉ diabetes ͉ fat droplet ͉ fat metabolism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
341
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(381 citation statements)
references
References 45 publications
(55 reference statements)
32
341
2
2
Order By: Relevance
“…Consistent with this observation, Cidec knockdown using RNA interference significantly stimulates lipolysis and results in the fragmentation of large storage lipid droplets to multiple small ones (Puri et al, 2007). Like perilipin, both Cidea and Cidec are regulated by PPARγ (Puri et al, 2008), and it is possible that the CIDE family proteins, similar to the PAT members, may play multiple roles in the formation of macrophage-derived foam cells.…”
Section: Cide Proteinsmentioning
confidence: 58%
“…Consistent with this observation, Cidec knockdown using RNA interference significantly stimulates lipolysis and results in the fragmentation of large storage lipid droplets to multiple small ones (Puri et al, 2007). Like perilipin, both Cidea and Cidec are regulated by PPARγ (Puri et al, 2008), and it is possible that the CIDE family proteins, similar to the PAT members, may play multiple roles in the formation of macrophage-derived foam cells.…”
Section: Cide Proteinsmentioning
confidence: 58%
“…Our gene-profiling analysis revealed that the expression of a number of lipogenic genes was significantly reduced in the liver of ROR␣ sg/sg mice. These included Cidec and Cidea, which regulate triglyceride storage, the size of lipid droplets, and lipolysis and which have been reported to be highly induced in hepatic steatosis (17,39,41). In addition, the expression of several genes implicated in the main pathway of triglyceride synthesis (37), including glycerol-3-phosphate acyltransferase (Gpam or Gpat1) and acyl-glycerol-3-phosphate acyltransferase 9 (Agpat9), and Mogat1, which is part of an alternative, less-studied pathway of triglyceride synthesis, was significantly reduced in liver of ROR␣ sg/sg mice.…”
Section: Discussionmentioning
confidence: 99%
“…FSP27 transcript is expressed in both human and murine white adipocytes (13,25) and is present at lower levels in murine brown adipocytes (13). In mice, CIDEA is found only in brown adipocytes (13,44), whereas in humans a high level of CIDEA is noted in white adipocytes (26). CIDEB transcript is markedly enriched in human and murine liver, with expression also reported for murine kidney and intestine (11,13,15).…”
mentioning
confidence: 88%